Epichloid endophytes confer resistance to the smut Ustilago bullata in the wild grass Bromus auleticus (Trin.) - Vignale, Maria Victoria (2013)
In this work it was studied for the first time whether asexual Epichloë (Neotyphodium) endophytes of Bromus auleticus, protect their host plants against the pathogenic fungus Ustilago bullata.Seeds of two different ecotypes of B. auleticus, one of them infected with the endophyte Neotyphodium pampeanum (NpE+) and the other infected with the endophyte Neotyphodium tembladerae (NtE+) and their respectively endophyte-free (NpE-/NtE-) counterparts were used. Seeds of each ecotype and endophytic status were superficially disinfected and were randomly assigned to different treatments named: S+ (smut fungus inoculated) and S- (mock-inoculated). It was evaluated the effect of U. bullata infection on plant characteristics in every stage of their life cycle: seedling emergence, vegetative growth, mortality and smut symptoms in the florets.In NtE+ infected plants, smut disease was almost completely suppressed, whereas in their endophyte-free counterparts (NpE-) the incidence of smut symptoms reached 64%. In NpE+ infected plants smut incidence was significantly lower (7%) than in endophyte-free plants (39%). Although U. bullata infection decreased the emergence rate of both endophyte-infected and endophyte-free plants, neutral or protective effects of the endophytes were observed in seedling development and survival. The survival during the first year of NtE+ plants was higher than in their NtE- counterparts.These results indicate a strong beneficial effect of vertically transmitted endophytes against this pathogen.